The potential of mangrove forest as a bioshield in Malaysia - Ghazali, N. (Institute of Electrical and Electronics Engineers Inc., 2016)
Using mangroves as a potential coastal bioshield has been intensively studied and tested in the past 10 years. Without a doubt, these studies suggest mangroves are able to attenuate waves thus make it perfect bioshield against tsunami, storm surges, erosion and other coastal disaster. This paper synthesis state of mangroves forests in Peninsular Malaysia towards the realisation of adopting mangrove as main coastal bioshield. Mangrove forest area degradation mainly caused by the land reclamation for agriculture and aquaculture. The situation has been exacerbated by the rapid growth of coastal communities that eventually become the potential victim for coastal disaster. Despite the rigorous effort to replant and rehabilitate, the incomplete hydrodynamic study of the site often leads to failure. An artificial structure like seawall and wave breaker for coastal defence are not sustainable anymore with the constant cost increment over the years. Though nurturing mangrove to serve as bioshield already begun before 2005, Malaysia commitment in mangrove bioshield officially become national agenda under "The Tenth Malaysia Plan 2010-2015", by the bill on "Climate adaptation: protecting the nation from the impact of climate change" and "Enhancing conservation of the nation's ecological assets". Now the implementation period has been concluded, further research in waves attenuation rate need to extend to precisely describe the capability of mangrove as bioshield in Peninsular Malaysia coastal.